Hiv and Covid - A recipe for disaster - Farhan, Zainab; Bashar , Nermeen; Khalid, Shantul (Journal of the Pakistan Medical Association, 2022)
To the editor, As the latest variant of Covid-19, OMICRON (B.1.1.529), makes its entry into Pakistan,1 one can’t help but wonder about the possibility of new strains emerging from this region of the world in particular Sindh. These fears stem from speculations amongst the scientific community over the variants possible emergence from an individual who was immune deficient; cancer, organ transplant or someone with uncontrolled HIV.2 Sindh not only has the highest number of Covid cases in Pakistan3 but also reported the first case of omicron a few days ago in Karachi.1 This coupled with the recent acquired immunodeficiency syndrome (AIDS) outbreak of 2019 in Sindh with around 751 of the 26,041 testing positive and 604(80%) of them being children is particularly worrisome. It must be kept in mind that these numbers are dangerously underreported. The performance of the Sindh AIDS Control Programme is under question as they fail to contain the outbreak.4 All this makes one worry about the cocktail of strains that are likely to emerge from Sindh. HIV remains silent for a number of years and majority of those infected are unaware of the disease until they develop AIDS. These immune compromised individuals have a higher risk of mortality associated with Covid-19. The virus lingers in their bodies for a longer period of time allowing it to mutate and develop new ways to evade the immune system.2,5 In order to prevent new variants from emerging from Sindh, which is more likely than not it is imperative that the local government amp up their vaccination efforts alongside intensified effort to end HIV as a health care problem. This can only be done with awareness programmes educating the masses on the disease, and its severity with co infection with Covid-19. Testing needs to be readily available free of cost and people encouraged to get tested. Information about safe sex and how the disease is transmitted needs to be conveyed to individuals all the while being respectful towards cultural and religious beliefs. It is important that the government work alongside healthcare professionals and the international community in dealing with this problem while it is still manageable at the risk of a deadly new variant emerging from this region.